Efficacy of Fractional Versus Fully Ablative CO2 Laser for Distolateral Onychomycosis: Experience With 20 Patients - Gnesotto, Laura; Piraccini, Bianca Maria; Starace, Michela; Naldi, Luigi; Mioso, Guido; Sechi, Andrea (Dermatology Practical & Conceptual, 2024)
Introduction: Oral antifungals are the treatment choice for onychomycosis, and topical therapies are favored in cases of limited nail involvement. Recently, carbon dioxide (CO2) laser treatment has emerged as an option to enhance the effectiveness of topical therapies. Objective: Our objective was to compare the efficacy of fractional ablative and fully ablative CO2 laser treatments for distolateral subungual onychomycosis affecting a single toenail and caused by dermatophytes. Method: The records of 10 patients treated with a single fully ablative CO2 session were matched with those of 10 patients who underwent a single CO2 fractional treatment. All had previously failed topical antifungal lacquers and were discharged with the prescription of topical ciclopirox nail lacquer (8%) for 3 months. Results: The overall clinical response was 80% versus 60% in the fully ablative compared to the fractional group, with a mean onychomycosis severity index drop of 6.9±5.4 in the fully ablative group and 3.6 ±6.6 in the fractional group computed from baseline to 8.6±1.6 weeks after treatment completion. The relapse rate among responders was 12.5% in the fully ablative and 33.3% in the fractional group after a mean follow-up time of 29.4±2.3 weeks. Conclusion: Fractional and fully ablative CO2 laser in combination with ciclopirox lacquer could increase theresponse rate in onychomycosis resistant to topical antifungals when systemic therapy is contraindicated or not yet pursued. Fully ablative mode therapy is significantly more effective than fractional (p<0.05). Further studies are needed to identify prognostic response factors and assess the long-term effectiveness of CO2 laser treatment.